Tackling macroeconomic risks: A case for stronger transatlantic cooperation - Amy Medearis; Klaus Günter Deutsch (Stiftung Wissenschaft und Politik (SWP), 2012)
The financial and economic crisis that was triggered by the collapse of Lehman Brothers in 2008 has vastly altered risk perception and management on both sides of the Atlantic. But the perception of macroeconomic and financial risks and policy responses do not always align in the United States and the European Union. In the US, policies have focused primarily on systemic financial and macro-prudential risk (e.g. risks from real estate, securities and banking markets); in the EU, the focus has been on risks stemming directly from the macro economy (e.g. economic and fiscal imbalances) and, in the context of the euro area, the adverse link between sovereign debt and the banking sector. While the US largely views itself as having exited the crisis, the EU is still mired in it, and this almost by definition puts the transatlantic partners in different positions going forward. Also, the euro area must address fundamental issues of its governance whereas the US must overcome political stalemate within the parameters of divided government. Nonetheless, the transatlantic partners have an interest in strengthening cooperation and coordination, even if this is not always easy
Keywords: 320